خدمة العملاء وتقييمها في بيت التمويل الكويتي بماليزيا : دراسة في ضوء أحكام الشريعة - كواملة، نور الدين عبد الكريم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study addresses the topic of customer service which is considered crucial in the field of modern financial transactions, at both the theoretical and practical levels. The objective of the study is to establish a link between the objectives of Shariʻah and customer service, followed by deriving all the relevant Shariʻah rulings. The study relies on both the descriptive and inductive methodologies in identifying the emergence of Customer Service and its relation with the services sector in general. Furthermore, the study sheds light on the discipline of objectives of the Shariʻah and its relation with the jurisprudence of transactions, the etiquettes of trading and social etiquettes in particular. The study reaches the conclusion that the field of customer service is built on theories and fundamental principles, which can be divided into ethical theories, administrative and institutional theories and individual professionalism theories. The study also concludes that the ethical and institutional theories can be categorized within the complementary objectives (al-maqasid al-ḥajiyyah), while the individual professionalism theories can be categorized within the desirable objectives (al-maqasid al-taḥsiniyyah). The study also derives a set of Shariʻah parameters related to the application and delivery of customer service, such as recognizing the rights of customers, protecting their privacy and confidentiality, maintaining punctuality and the overall appearance. In addition, to the general requirements of being honest and in compliance with Sharīʻah related etiquette in dealing with customers and avoiding any form of manipulation. The study analyzes two practical models related to the applications of customer service; the Consumer Protection Law of Malaysia and the applications of Kuwait Finance House in Malaysia in regards to customer service. The study concludes that the Consumer Protection Law of Malaysia is in conformity with the objectives of Sharīʻah. As for Kuwait Finance House, the study observes the eagerness of the institution in providing excellent customer service as promised by them. However, the study highlights some observations related to their customer service that needs urgent re-evaluation, such as the duration for replying to customer complaints is 15 days which can be considered as unacceptable. Finally, the study tries to provide some solutions for the above-mentioned observations.